Hydrodynamic Performance Evaluation of a Double Stage Savonius Turbine on River Ogun, South-Western Nigeria - Babatunde, Moses Adeniyi; Ladokun, Laniyi Laniran; Oke, M A (Mekanika: Majalah Ilmiah Mekanika, 2025)
This study evaluates the hydrodynamic performance of a double-stage Savonius hydrokinetic turbine with a rotor diameter of 0.3m, a rotor height of 0.6m, and a swept area of 0.18 m², designed for deployment in the River Ogun, Southwestern Nigeria. The objective is to assess the turbine's suitability for harnessing energy from low-head rivers. The methodology involved testing the turbine in a riverine environment at selected flow velocities and depths, evaluating its power coefficient (Cp), Tip Speed Ratio (TSR), and power output. The results show that the turbine achieves a maximum Cp of 0.321 at a TSR of 0.5 and a peak power output of 100.9 W at a flow velocity of 1.55 m/s and angular velocity of 5.26 rad/s, and with a cut-in speed of approximately 1.48 m/s. Across all test conditions, the average Cp was approximately 0.3013, indicating an energy conversion efficiency of about 30.1% relative to the total available kinetic power, which is 335.15 W. This result highlights the double-stage Savonius turbine’s capacity to extract energy under ultra-low head and low-velocity conditions efficiently and highlights the importance of optimizing turbine design and operating conditions for improved energy generation efficiency.